Fluorescent Imidazo[1, 2‐a]pyrimidine Compounds as Biocompatible Organic Photosensitizers that Generate Singlet Oxygen: A Potential Tool for Phototheranostics. Issue 20 (28th January 2021) - Lima, Maria L. S. O.; Braga, Carolyne B.; Becher, Tiago B.; Odriozola‐Gimeno, Mikel; Torrent‐Sucarrat, Miquel; Rivilla, Iván; Cossío, Fernando P.; Marsaioli, Anita J.; Ornelas, Catia
Abstract: Photodynamic therapy has been used to treat a variety of diseases, however, there is continuing search for new biocompatible photosensitizers. Herein, we demonstrate for the first time that imidazo[1, 2‐ a ]pyrimidine compounds are able to generate singlet oxygen species and can act as photosensitizers in the intracellular environment. Our results show that this class of compounds absorb and emit in the 400–500 nm region, present low cytotoxicity in the dark, are efficiently uptaken by cells, are fluorescent in intracellular medium, and generate singlet oxygen upon irradiation, killing cancer cells within 2 h at low concentration (2.0 μm ). The imidazo[1, 2‐ a ]pyrimidine compounds are a potential new tool for phototheranostics, because they can be simultaneously used for fluorescence imaging and photodynamic therapy. Abstract : New phototheranostics ! Imidazo[1, 2‐ a ]pyrimidine compounds are able to generate singlet oxygen species and act as photosensitizers in the intracellular environment (see figure). They exhibit all the properties of an ideal photosensitizer, required for simultaneous fluorescence imaging and photodynamic activity, and as such they have potential for phototheranostics.